Pemberdayaan masyarakat Desa Benan dalam peningkatan mutu Teripang sebagai komoditas unggulan desa melalui sosialisasi penanganan pascapanen - T. Ersti Yulika Sari; Sri Novalina Amrizal; Wahyu Muzammil; Yulia Oktavia; Tetty Tetty; Khairunnisa Khairunnisa; Dwi Septiani Putri; Aidil Fadli Ilhamdy; Azwin Apriandi; Aminatul Zahra; R. Marwitta Sari Putri; Jumsurizal Jumsurizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Sea cucumbers which have the scientific name Holothuroidea are fishery commodities that have high economic value and are in great demand in the global market. Sea cucumbers are the main commodity of Benan Village which is the outermost island of Lingga district. Most of the people in Benan Village work as sea cucumber fishermen. As an aquatic resource owned by the village, sea cucumbers are still constrained in terms of handling so that it reduces the selling value of the dried sea cucumbers produced. Therefore, it is important to empower the people of Benan Village regarding the postharvest handling of sea cucumbers which aims to improve the quality as well as directly increase the selling value of that resources. Community empowerment activities are expected to add insight and improve the ability of the Benan Village community in handling sea cucumbers post-harvest. Empowerment was carried out through three methods, namely the distribution of questionnaires and discussions in the form of questions and answers with the Benan Village community group regarding the problem process in handling post-harvest sea cucumbers, which was carried out after distributing questionnaires to the sea cucumber aquaculture community, then education and discussion on good procedures were carried out in post-harvest handling. To improve the quality of this sea cucumber commodity, then in the third stage, mentoring and practice regarding the correct handling of sea cucumbers is carried out to produce good quality sea cucumbers from washing to packaging. The selection of discussion methods, lectures/education, and direct practice is considered effective in increasing public knowledge about the process of handling sea cucumbers postharvest properly and correctly, considering that the target stakeholders are sea cucumber farmers.